Climate change education: following the information - Puttick, SP; Chandrachud, P; Chopra, R; Robson, J; Singh, S; Talks, I (Routledge, 2022)
This chapter explores, through a fictionalised story, the nexus of information, climate change, digital geographies, children’s geographies, and the future of work. We repurpose a follow-the-thing methodological approach (Cook et al., 2017), normally used for commodities, by applying it to information to tell a story about the journeys of information – or digital non-objects (Rose, 2016) – about climate change. In one direction the story moves ‘backwards’ from the classroom, tracing the interfaces, networks, and frictions through which this information moves and transforms. In another direction, the story moves ‘forwards’ out of the classroom into the lives of the children to whom it was taught. Children’s educational experiences are increasingly digitally mediated, and the unprecedented amounts of information available to teachers presents significant challenges for curriculum making. Children and young people are calling for greater attention to be given to climate change education, and this story highlights opportunities for rethinking the ways in which information about climate change should be navigated to help work towards more equitable, just, and sustainable futures.